2022
DOI: 10.3389/fbioe.2022.905438
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Extracellular Matrix-Based Bioinks for 3D Bioprinting

Abstract: As a microenvironment where cells reside, the extracellular matrix (ECM) has a complex network structure and appropriate mechanical properties to provide structural and biochemical support for the surrounding cells. In tissue engineering, the ECM and its derivatives can mitigate foreign body responses by presenting ECM molecules at the interface between materials and tissues. With the widespread application of three-dimensional (3D) bioprinting, the use of the ECM and its derivative bioinks for 3D bioprinting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 153 publications
0
18
0
Order By: Relevance
“…Thus, dECM‐derived bioinks, which facilitate the retention of the natural ECM complexity that promotes cell activity and tissue regeneration, have been introduced. [ 20 , 44 , 45 ] However, the low viscosity of the dECM bioink leads to weak formability and makes manufacturing complex structures difficult. [ 30 , 46 ] To address this issue, in this study, dECM was incorporated into a GelMA hydrogel to form a hybrid bioink.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, dECM‐derived bioinks, which facilitate the retention of the natural ECM complexity that promotes cell activity and tissue regeneration, have been introduced. [ 20 , 44 , 45 ] However, the low viscosity of the dECM bioink leads to weak formability and makes manufacturing complex structures difficult. [ 30 , 46 ] To address this issue, in this study, dECM was incorporated into a GelMA hydrogel to form a hybrid bioink.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, decellularized extracellular matrix (dECM) bioink has attracted widespread attention. [ 19 , 20 ] Studies have demonstrated the benefits of tissue‐specific dECM bioinks, such as recreating the intrinsic ECM complexity of native tissues, mimicking ECM composition or resident cytokines, and enhancing stem cell differentiation into a specific lineage. [ 21 , 22 , 23 ] 3D bioprinting based on dECM bioink has made great progress in heart, muscle, cartilage, skin and kidney regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The center regions of the molecules and the determinant polypeptide structures in the three spiral chains are what cause collagen’s low antigenicity. Its use in biological domains has been severely constrained by this defect [ 43 ]. An example is the use of a type I collagen–gelatin hydrogel for ocular tissue engineering by Goodarzi et al [ 66 ] in 2019.…”
Section: Current Status Of Polymers Used In Corneal Stromal Regenerationmentioning
confidence: 99%
“…Although dECM-based bioinks have poor mechanical properties, there are studies where they only use the dECM for the bioink [ 73 , 75 , 76 ]. In order to improve the properties of the scaffolds, the bioinks combine different biomaterials, or/and they may need an additional supporting structure in order to be able to achieve increasingly intricate 3D models [ 74 , 77 ].…”
Section: Tendon-derived Decm Bioinksmentioning
confidence: 99%